Late Onset CNS Immune Reconstitution Inflammatory Syndrome in an Immunocompetent Patient - Hornik, Alejandro; Rodriguez-Porcel, Federico; Wallery, Shawn; Flaster, Murray; Lee, John; Biller, Jose (Frontiers in Neurology, 2013)
IRIS refers to the presence of paradoxical clinical deterioration attributable to immune system recovery during highly active antiretroviral therapy (HAART). We present an immunocompetent patient with multifocal leukoencephalopathy on HAART, with central nervous system (CNS) IRIS pathology of unknown infectious etiology. CNS IRIS pathology should be suspected in patients on longstanding HAART without immune reconstitution, presenting with unexplained leukoencephaphalopathy.